Policy and Legal Issues Involved in Successful Implementation of Joint forest Management (JFM) - a Critical Analysis - Upadhyay, R. K. (Indian Forester, 2001)
The author is of the opinion that protecting forests under sole ownership of government in past along with policing approach has not given desired result. Hence protection and regeneration of forest may be tried under co-ownership (joint ownership) of government ,nd village community on experimental basis where JFM is being implemented. On seeing the result of co-ownership, it can be expanded to other areas.